Formulation of Dry Powders for Inhalation Comprising High Doses of a Poorly Soluble Hydrophobic Drug - Tarara, Thomas E.; Miller, Danforth P.; Weers, Audrey E.; Muliadi, Ariel; Tso, Jerry; Eliahu, Avi; Weers, Jeffry G. (Frontiers in Drug Delivery, 2022)
Spray-dried formulations of a hydrophobic, crystalline drug, GDC-A, were prepared using the suspension-PulmoSphere™ technology. Increases in drug loading resulted in decreases in the primary particle size distribution and increases in tapped density. This enabled fine particle doses of up to 25 mg to be achieved with a portable dry powder inhaler from a size 3 capsule. The powders were physically and chemically stable, with no changes in physical form or degradants observed during processing or on storage in an open configuration at 40 C for one month. The potential benefits of the suspension-based spray drying process relative to solution-based spray drying in terms of stability, lung targeting, and safety/tolerability are discussed.